1996
DOI: 10.1177/0734242x9601400103
|View full text |Cite
|
Sign up to set email alerts
|

Physico-Chemical Characterization and Leaching of Desulphurization Coal Fly Ash

Abstract: Fly ash produced by coal combustion using two types of desulphurization process were studied: a conventional pulverized coal boiler equipped with lime injection (PCL ash), and a circulating fluidized bed combustion boiler with limestone injection (CFBC ash). The ashes were characterized completely: granulometry, morphology, mineralogy, chemical composition and behaviour to water contact. Both PCL ash and CFBC ash present similar features: fine granulometry, presence of anhydrite phase and sulphate content. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 5 publications
0
20
0
Order By: Relevance
“…This concurs with Hower et al (1996), who reported that arsenic concentrations in the base material and subsequent levels of leaching are not directly related. A more important factor may be that trace metals such as arsenic, molybdenum, and vanadium are bound through chemical reactions occurring during the hardening of concrete (Lecuyer et al, 1996). This binding process may also account for the lower leaching of uranium from concrete compared with granite even though uranium was present in approximately equal concentrations in both base materials.…”
Section: S254mentioning
confidence: 93%
“…This concurs with Hower et al (1996), who reported that arsenic concentrations in the base material and subsequent levels of leaching are not directly related. A more important factor may be that trace metals such as arsenic, molybdenum, and vanadium are bound through chemical reactions occurring during the hardening of concrete (Lecuyer et al, 1996). This binding process may also account for the lower leaching of uranium from concrete compared with granite even though uranium was present in approximately equal concentrations in both base materials.…”
Section: S254mentioning
confidence: 93%
“…[6,7] However, the resultant CFBC fly ashes (CFAs) distinctly differ from the conventional pulverized coal combustion fly ashes (PFAs) in physical and chemical characteristics. [8,9] While the majority of PFAs could be utilized in construction materials such as cement and concrete, [9,10] the disposal of the increasing amount of CFAs still poses challenges such as highly exothermic behavior on wetting, highpH leachate, and excessive expansion in landfill, etc. [11] Generally, CFAs do not conform to either North American standards nor European ones as components or additives to concretes.…”
Section: Introductionmentioning
confidence: 99%
“…Chemicals which partake in leaching are also waste heavy metals condensed on fly ahs particles, which change into a gaseous state during combustion, and as a result of precipitation on dry waste dumps and due to the contact with process water on wet waste dumps, they are washed off from the surface of the particles and penetrate into the soil and ground water, and then to living organisms. If the deposited waste has an alkaline reaction, then the main environmental hazard will be posed by liberating sodium, potassium and calcium sulphates (Lecuyer et al, 1996). A particular danger is caused by acid precipitation which, due to its aggressiveness, promotes the solubility of those compounds.…”
Section: +mentioning
confidence: 99%